Establishment of patient-derived cancer xenografts in immunodeficient NOG mice - CHIJIWA, TSUYOSHI (Int J Oncol, 2015)
Viable and stable human cancer cell lines and animal models combined with adequate clinical information are essential for future advances in cancer research and patient care. Conventional in vitro cancer cell lines are commonly available; however, they lack detailed information on the patient from which they originate, including disease phenotype and drug sensitivity. Patient-derived xenografts (PDX) with clinical information (so-called ‘cancer xenopatients’) are a promising advance that may accelerate the development of anticancer therapies. We established 61 PDX lines from 116 surgically removed tumor tissues inoculated subcutaneously into NOG mice (53% success rate). PDX lines were established from various types of epithelial tumors and also from sarcomas, including gastrointestinal stromal tumors and Ewing/PNET sarcomas. The metastatic tumors yielded PDX lines more effectively (65%) than the primary tumors (27%, P<0.001). In our PDX models, morphological characteristics, gene expression profiles, and genetic alteration patterns were all well preserved. In eight cases (7%), the transplantable xenografts for several generations were composed of large monotonous nonepithelial cells of human origin, revealed to be Epstein-Barr virus infection-associated lymphoproliferative lesions. Despite this, PDX linked with clinical information offer many advantages for preclinical studies investigating new anticancer drugs. The fast and efficient establishment of individual PDX may also contribute to future personalized anticancer therapies.